If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(a + -8) = 28 + -5a Reorder the terms: 7(-8 + a) = 28 + -5a (-8 * 7 + a * 7) = 28 + -5a (-56 + 7a) = 28 + -5a Solving -56 + 7a = 28 + -5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5a' to each side of the equation. -56 + 7a + 5a = 28 + -5a + 5a Combine like terms: 7a + 5a = 12a -56 + 12a = 28 + -5a + 5a Combine like terms: -5a + 5a = 0 -56 + 12a = 28 + 0 -56 + 12a = 28 Add '56' to each side of the equation. -56 + 56 + 12a = 28 + 56 Combine like terms: -56 + 56 = 0 0 + 12a = 28 + 56 12a = 28 + 56 Combine like terms: 28 + 56 = 84 12a = 84 Divide each side by '12'. a = 7 Simplifying a = 7
| 9+c=-18 | | -34=-45 | | 4(3x+1)=24 | | 1-5b=2-4b | | 2-5p=22 | | 3x-16=-41+8x | | e+(-4)=7 | | 3x^3+10x^2-4x-35=0 | | x^2+3x^2+2x= | | 3n+2n=5 | | X+-4.2=-3 | | x^5-4x^4+x^3-7x+1=0 | | -91=p-6(-p+7) | | -17x-23x=12x-2 | | -17x-23x=12x-2 | | x^2-x-6%x^2-5x+6 | | f(x)=zx^2+12x+14 | | 2(u-8)-1=-5(-5u+4)-5u | | (-15)+e=12 | | 12x=121 | | 45-2x(15-2)= | | 3v-12=2 | | 3x^20=41 | | 8(3m+1)= | | 5(-x+10)=5x+10 | | x+37=7 | | 19=-3.1+j | | 3(12)=y | | -8n+4(1+5a)=-6n-14 | | x-z=15 | | 6z+1=.30 | | -6(6n+5)=38-2n |